Lust : What We Know About Human Sexual Desire. - Regan, Pamela C. C. (Sage series on close relationships., 1999)
Accessibly written, this interdisciplinary book reviews theory and research on the characteristics of sexual desire, the individual physical and mental factors that influence the experience of sexual desire (hormones, age, gender, beliefs, mood), the various partner characteristics that incite sexual desire (attractiveness) and the association between sexual desire and interpersonal, relational events and experiences (romantic love). The book concludes with an examination of the personal, interpersonal and societal implications of sexual desire. Throughout, the authors draw on findings from th.